AB0637 Iloprost (ILO) in Systemic Sclerosis (SSC): The Safety Experience of Two Italian Centres. (15th July 2016) - Guiducci, S.; Bellando-Randone, S.; Bruni, C.; Giuggioli, D.; Colaci, M.; Lumetti, F.; Lepri, G.; Fiori, G.; Bartoli, F.; Ferri, C.; Matucci-Cerinic, M.
Abstract : Background: Iloprost (ILO) is a synthetic analogue of prostacyclin PGI2 with a potent vasodilator action, an anti-proliferative effect on smooth muscle cells and inhibition of platelet aggregation. ILO is employed intravenously for the control of Raynaud Phenomenon and digital ulcers. Up to now, no agreement has been reached on the regimen (dosage and frequency) to be used in SSc patients. Objectives: To identify the most common side effects that are developed during ILO infusion in SSc. Methods: 81 SSc patients, classified according to ACR EULAR criteria, derived from two Italian centers, were submitted to ILO infusion: patients were subclassified according to the edematous or fibrotic/atrophic phase of the disease. ILO was infused (6–8 hour infusion, dose ranging from 0.5 to 1.0 ng/kg/ min) (1) with a progressive increase of the dosage up to the achievement of patient's tolerance: the infusion on pump was started at 5 ml/hour and increased every half an hour up to 20 ml/hour (a dose of 4 mcg/h which corresponds to 1ng/kg)according to patients tolerance and appearance of side effects. Results: Out of 81 patients, 16 were in the edematous phase with puffy fingers (digital edema). In this cohort, 5 individuals (31.2%) developed diarrhea and 9 (56.2%) developed hypotension during the infusion. When the drug was withdrawn patients had an immediate amelioration but when ILO was restarted, they again developed diarrhea or hypotension that led to definitive interruption of the treatment. Moreover, 10/16 patients (62.5%) experienced significant and painful digital swelling which led to the tapering of the infusion dosage below 10 ml/hr (which corresponds to 0.5 ng/kg per min); out of 10 patients, only one could continue the treatment while the other 9 had to be withdrawn due to the maintenance of the intense digital pain due to vasodilation. Finally, 11 patients (68.7%) reported flushing and 7 (43.7%) headache, but they were always controlled with the reduction of the infusion below 10 ml/hr. Out of 81 patients, 65 were in the atrophic/ fibrotic phase: 10 patients (15.3%) developed diarrhea and 24 pts (37%) hypotension that led to temporary withdrawal: when ILO was restarted and kept below 10 ml /hr, no side effects were experienced. In 23 cases (35.3%) flushing and in 8 cases (12.3%) headache were experienced, but were well controlled with infusion reduction below 10 ml/hr. Conclusions: ILO was well tolerated in SSc patients characterized by fibrotic phase, where side effects could be managed by reducing/modulating the infusion rate. In edematous patients, ILO infusion should be decided in case where the severity of Raynaud's phenomenon or the presence of digital ulcers strongly suggests its use. References: Wigley FM, et a Intravenous iloprost infusion in patients with Raynaud phenomenon secondary to systemic sclerosis. A multicenter, placebo-controlled, double-blind study Ann Intern Med. 1994;120:199–206 Disclosure of Interest: None declared